IMPORTANCE OF UZBEK NATIONAL MUSICAL INSTRUMENTS IN FOLKLORE ART - Babamurodov Eshmamat Kamilovich (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: This article is about the historical origin of Uzbek national musical instruments and their formation today. In the article, the basis of musicology is about Uzbek musical instruments, their notation, the importance of solo and orchestra performance, and the article provides information about them.